2017
DOI: 10.1007/s00520-017-3980-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of reinfusion of concentrated ascitic fluid for malignant ascites: a concept-proof study

Abstract: The effects of reinfusion of concentrated ascitic fluid may be maintained for 1 month, being potentially longer than that of total paracentesis alone. This study had no comparison groups and examined the short-term effect. A randomized controlled study to compare the long-term effects of total paracentesis alone vs. CART is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…In the overall CART procedure, the most common AEs were fever and fever-related symptoms, such as chills after the reinfusion of concentrated ascites. The frequency of fever in this study, 5.6% (13 events), was comparable to that in previous studies, 5-16.4% [8,11,16,17]. The average increase in body temperature was reported to be 0.1-0.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the overall CART procedure, the most common AEs were fever and fever-related symptoms, such as chills after the reinfusion of concentrated ascites. The frequency of fever in this study, 5.6% (13 events), was comparable to that in previous studies, 5-16.4% [8,11,16,17]. The average increase in body temperature was reported to be 0.1-0.…”
Section: Discussionsupporting
confidence: 87%
“…Fever is a transient and mild AE in CART; however, its management is still important and valuable because CART is usually performed as a palliative therapy [1,11]. Especially in cancer patients, the characteristics and contents of reinfused concentrated ascites vary according to those of the original ascites and modi cation through the CART procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As almost all studies on CART are case series with no set controls, evaluating the clinical merits of CART is difficult 31 . Even controlled comparisons with simple paracentesis, which is the most common non-drug treatment for ascites 17,18 , have not been conducted 32 . The objective of the current investigation was to verify the serum albumin elevating effect of CART by controlled study with simple paracentesis.…”
Section: Introductionmentioning
confidence: 99%
“…There have been only a limited number of studies on the palliative management of patients with malignant-related ascites; many of them chose overall survival, puncture-free survival, time to the next paracentesis, signs and symptoms related to ascites, and common terminology criteria for adverse events as outcomes, but few assessed patient-reported outcomes with validated tools. 2,5,6,23,24 Given the weak evidence supporting the efficacy of treatment modalities for symptomatic malignant-related ascites, clinical trials with the utilization of validated patient-reported outcomes are urgently needed. 1,3 The validation of the ESAS:AM may facilitate such initiatives in the future.…”
Section: Discussionmentioning
confidence: 99%